“L’Homme” as a Cornerstone of Descartes’ Anthropology - Khmil, Volodymyr; Malivskyi, Anatolii (Studia Warmińskie, 2018)
According to the authors, in the current research on the legacy of Descartes, the significance of the text left by Descartes in the form of an unfinished text L’Homme has not yet been sufficiently appreciated. The analysis of this dissertation makes it possible to see that for Descartes, which this philosopher expressed especially in the early period of his activity, the worldview issues were of priority, and in particular the understanding of man and his place in reality. On the basis of the analyzes carried out, the authors conclude that in all of Descartes’ work, even those that do not directly refer to anthropological issues and raise physics issues, there is a vision of the man Descartes sketched in L’Homme.